Insentif Pajak Covid-19, Kepatuhan Wajib Pajak, Omnibus Law Perpajakan dan Penerimaan Pajak - Nofriani, Sherli; Putri, Adriyanti Agustina; Aristi, Mentari Dwi (E-Jurnal Akuntansi; Vol 32 No 12 (2022)DO - 10.24843/EJA.2022.v32.i12.p12, 2022)
Indonesia's tax revenue in 2017-2021 has fluctuated so it is necessary to know the factors that affect tax revenue. The purpose of the study was to find out and analyze the effect of Covid-19 Tax Incentives, Taxpayer Compliance and Tax Omnibus Law on Tax Revenues at KPP Madya Pekanbaru 2020-2021. The methods of this thesis is a descriptive statistical analysis, data quality test, classical assumption test and hypothesis test. Independent Variables are Covid - 19 Tax Incentives, Taxpayer Compliance and Omnibus Law taxation while the Dependent Variables are Tax Revenues. The total population in this study is 1,296 corporate taxpayers using random sampling and eliminated using the slovin formula, obtained 93 sample respondents. The research is quantitative with cross-section primary data in the form of likert-scale questionnaires. The results showed that the Covid-19 Tax Incentive Variable, Taxpayer Compliance and Tax Omnibus Law had a positive effect on Tax Revenue at the Pekanbaru Intermediate KPP for 2020 - 2021 . Keywords: Covid-19; Incentives; Obedience; Omnibus Law